2013
DOI: 10.1039/c3cc42534g
|View full text |Cite
|
Sign up to set email alerts
|

Ln[N(SiMe3)2]3-catalyzed cycloaddition of terminal alkynes to azides leading to 1,5-disubstituted 1,2,3-triazoles: new mechanistic features

Abstract: The first example of rare earth metal-catalyzed cycloaddition of terminal alkynes to azides resulting in the formation of 1,5-disubstituted 1,2,3-triazoles is described. Preliminary studies revealed that the present cycloaddition shows unprecedented mechanistic features involving a tandem anionic cascade cyclization and anti-addition across the C≡C triple bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(51 citation statements)
references
References 58 publications
0
50
1
Order By: Relevance
“…Recently, a seminal example of rare earth-metal-catalyzed AAC reaction with terminal alkynes leading to 1,5-disubstituted 1,2,3-triazoles was described by Zhou's group [110]. Optimization of the reaction conditions showed that the presence of 10 mol% nBuNH 2 improved the yield (Fig.…”
Section: The Lnaac Reactionsmentioning
confidence: 99%
“…Recently, a seminal example of rare earth-metal-catalyzed AAC reaction with terminal alkynes leading to 1,5-disubstituted 1,2,3-triazoles was described by Zhou's group [110]. Optimization of the reaction conditions showed that the presence of 10 mol% nBuNH 2 improved the yield (Fig.…”
Section: The Lnaac Reactionsmentioning
confidence: 99%
“…The overall free energy barrier, that is associated to the transfer of the alkyne proton on the ligand, is rather low (11.1 kcal/mol). Assuming that the protonated ligand is easily displaced by the incoming azide, we have investigated the B to E transit as proposed by Zhou and coworkers [15] (see Figure 4b). No low-energy pathway connecting B to D was found.…”
Section: Resultsmentioning
confidence: 98%
“…Recently, Zhou and coworkers published the first example of rare-earth catalyzed cycloadditions between terminal alkynes and terminal azides, resulting in the formation of 1,5-disubstituted 1,2,3-triazoles. [15] The catalytic systems that they used consist in a complex of the type Ln[N(SiMe 3 ) 2 ] (Ln, Y, Nd, Sm, Gd) in the presence of n-BuNH 2 . This report incited us to computationally explore their proposed mechanism of Figure 4, using the same modelization approach as used above and considering the Y[N(SiH 3 ) 2 ] 3 (YL 3 ) simplified precatalyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[361] Other catalysts apart from Cu I or Ru II for the synthesis of 1,4-or 1,5-substituted 1,2,3-triazoles comprise NiCl 2 , PdCl 2 , PtCl 2 , [473] a silver complex, [474] and rare earth metal amides. [475] The Ce(OTf) 3 -catalyzed [3+2]-cycloaddition reaction between organic azides and nitroolefins proceeds with elimination of HNO 2 selectively producing 1,5-disubstituted 1,2,3-triazoles in high yield (Equation (17)). [476] In continuation of our studies on the reactions of metal azides with alkynes, [142] we anticipated that reactions of metal alkynes with organic azides should lead to metal-C bound triazolyls.…”
Section: Reactions Of Main Group Element Azides With Alkynesmentioning
confidence: 99%